License to wed : what legal marriage means to same-sex couples - Richman, Kimberly D. (New York University Press, 2014)
A critical reader of the history of marriage understands that it is an institution that has always been in flux. It is also a decidedly complicated one, existing simultaneously in the realms of religion, law, and emotion. And yet recent years have seen dramatic and heavily waged battles over the proposition of including same sex couples in marriage. Just what is at stake in these battles? This book examines the meanings of marriage for couples in the two first states to extend that right to same sex couples: California and Massachusetts. The two states provide a compelling contrast: while inches.